The ultimate IQ testbook:1,000 practice test questions to boost your brain power - Carter, Philip; Russell, Ken (New Delhi : Kogan Page India Pvt. Ltd., 2008)
Working through the questions can help you to improve your vocabulary and develop powers of calculation and logical reasoning. It has also been proved that by studying the different types of test, and recognizing the different types of questions, you can improve your test performance.
Keywords: Intelligence tests; Aptitude tests